2015
DOI: 10.5194/nhess-15-2143-2015
|View full text |Cite
|
Sign up to set email alerts
|

Attributing trends in extremely hot days to changes in atmospheric dynamics

Abstract: Abstract. This paper presents a method for attributing regional trends in the frequency of extremely hot days (EHDs) to changes in the frequency of the atmospheric patterns that characterize such extraordinary events. The study is applied to mainland Spain and the Balearic Islands for the extended summers of the period 1958-2008, where significant and positive trends in maximum temperature (T x ) have been reported during the second half of the past century.First, the study area was split into eight regions at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…However, regional studies show some variation in results. The upward trends of hot days occurrence have been shown in most studies, among others for the area of Switzerland [98], Turkey [99], and Spain [100], while there are countries for which no statistically significant trend of changes was recorded, incl. for New Zealand [101], or even a slight downward trend in the number of hot days, as in China [102].…”
Section: Discussionmentioning
confidence: 88%
“…However, regional studies show some variation in results. The upward trends of hot days occurrence have been shown in most studies, among others for the area of Switzerland [98], Turkey [99], and Spain [100], while there are countries for which no statistically significant trend of changes was recorded, incl. for New Zealand [101], or even a slight downward trend in the number of hot days, as in China [102].…”
Section: Discussionmentioning
confidence: 88%
“…The slope of these extents is 0.0088, more than double the slope of the extents based on daily temperatures. In addition to the increasing trend, this plot permits us to identify years which were colder with respect to the trend, and with a lower variability, for example, 1972, 1977, 1984, or hotter as year 2003 (García‐Valero et al, 2015). In the last decade, two different types of behaviours are observed, the distribution of the extent in some years is quite high, centred around 0.9, while others centred around 0.5.…”
Section: Results For the Space–time Analysismentioning
confidence: 99%
“…For instance, Horton et al (88) attributed much (∼75%) of the recent increases in cold extremes over central Asia to a robust increase in "ridge-trough" pairs (see 88, figures 4b,f ), reasonably explaining the phenomena deviated from the prevalent warming backdrop. García-Valero et al (89) reported a fairly high contribution (∼50%) of changes in circulation patterns in determining trends of hot extremes in Spain and the Balearic Islands. Chang et al (90) revealed that the weakening activity of extratropical cyclones led to the warming of maximum temperature in the mid-latitudes in Northern Hemisphere.…”
Section: Changes In Dynamic Drives: Large-scale Circulation Patternsmentioning
confidence: 99%